Decisional balance, stages of change and use of contraceptive methods among adolescents in the immediate postpartum period: a descriptive correlational study - Benavides-Torres, Raquel (2024)
Introduction: Pregnancy in adolescents due to the non-use of contraceptives constitutes one of the main public health problems. The immediate puerperium provides the opportunity to evaluate the behavior before, during and after the decision-making in the use of contraceptives to avoid subsequent pregnancies. Objective: To determine the association between the characteristics of the adolescent, the decisional balance, and the stages of change in the use of contraceptive methods in adolescent mothers in the immediate postpartum period. Materials and methods: Descriptive-correlational and cross-sectional design, census sampling, sample size of 293 adolescent mothers between 12 and 24 years of age in the immediate postpartum period, estimated for a multiple linear regression test with 8 covariates, significance level of 0,05, coefficient determination of R2=0,09 and power of 90%. Results: 80,50% are in the Preparation phase, being the hormonal implant the most accepted. Correlation between years of study (rs=-0,16; p<0,01) and perceived disadvantages in the use of contraception. Years of study in postpartum adolescent mothers explained 16% of the variance (F=5,602; p=0,018) in the disadvantages of contraceptive use (β=-0,247; p<0,01). Discussions: Based on the findings, the Transtheoretical Model of Change was useful in identifying the stages of change in adolescent mothers. Conclusion: It would be worth strengthening more preventive strategies adapted for adolescents in the immediate postpartum period with a school lag.